Telemedicine and the Interdisciplinary Clinic Model: During the COVID-19 Pandemic and Beyond. (October 2020) - Zughni, Lisa A.; Gillespie, Amanda I.; Hatcher, Jeanne L.; Rubin, Adam D.; Giliberto, John Paul
The emergence of the novel coronavirus disease 2019 (COVID-19) and the subsequent need for physical distancing have necessitated a swift change in health care delivery. Prior to the COVID-19 outbreak, many institutions utilized an interdisciplinary clinic model including both a laryngologist and a speech-language pathologist for the evaluation of patients with voice, swallowing, and upper airway disorders. To improve access, many providers are pursuing the use of interdisciplinary telemedicine to provide individualized patient-centered care while allowing for physical distancing. The purpose of this commentary is to review the current literature regarding telemedicine in laryngology and speech-language pathology as well as the current and future states of practice for interdisciplinary tele-evaluations.